Primary seismic refraction data during cruise RV SONNE SO258/2 (INGON), Indian Ocean off Sri Lanka, profile AWI-20170300 ... - Weigelt, Estella; Geissler, Wolfram H; Altenbernd-Lang, Tabea; Jokat, Wilfried; Werner, Reinhard (PANGAEA, 2025)
As part of the research project INGON (a collaboration between the Alfred Wegener Institute and the GEOMAR), two offshore seismic refraction profiles were obtained during Sonne cruise SO258 to study the separation of India and Antarctica. The presented data set covers data of 30 stations recorded with three different types of Ocean Bottom Seismometer (OBS)-systems: 12 LOBSTER and 2 NAMMU systems of the AWI belonging to the DEPAS pool (German Instrument Pool for Amphibian Seismology) and 20 OBS systems of GEOMAR. The instruments were deployed at an average distance of 11.5 km along a straight profile running perpendicular to the shore. Profiling started on 22 July 2017 at 80.99941°N, 5.814°E, and ended on 23 July 2017 at 80.99998°N, 2.43193°E. All OBS could be synchronized with the GPS clock upon recovery such that skew values describing the clock drift are available for all stations. One station did not return data. The data set provides primary data of OBS-stations concerning the refraction seismic profile ...